PEMANFAATAN INSTAGRAM AKUN @INSPIRA.SIEN DALAM MENUNJANG KOMUNIKASI PARA PENYINTAS PENYAKIT KRONIS - Kusumawardhani, Okta Annisa; Candrasari, Yuli (Ilmu Komunikasi, FISIP Universitas Pasundan, 2024)
The existence of social media, especially Instagram, facilitates forms of interaction between individuals. The convenience of the various features available on Instagram also makes it easier for users to interact with each other and form networks, which ultimately forms a virtual community. One of the virtual communities on Instagram social media is the community of chronic disease fighters and survivors, Inspira.sien. Inspira.sien is a fairly large community in Indonesia with the first patient assistance services, which also houses several communities of survivors of certain specific chronic diseases. In interacting using Instagram, survivors have the same goals and similarities in an Inspira.sien community. This research aims to examine how the social media Instagram is used by survivors of chronic illnesses to interact and provide support to each other in a community called Inspira.sien, as well as what impact this community has on the survivors. This research uses the theory of Computer Mediated Communication (CMC), Electronic Propinquity Theory, and Social Media which uses qualitative methods with a netnographic approach. Data was obtained by conducting in-depth interviews and observations, where the informants taken were Inspira.sien followers who were also survivors of chronic illnesses. The results of this research show that the form of interaction that occurs by survivors in the Inspira.sien community on Instagram social media using existing features such as feeds, reels, and Instagram stories is able to provide communal attachment and closeness between its members and make them feel related to each other. Keywords : Virtual Community, Chronic Illness, CMC